Community based crop risk reduction through the adoption of climate smart agriculture practices in Haryana - Rajesh Kumar1; Mehtab Singh; Sandeep (National Geographical Journal of India, 2024)
Agriculture in India is highly sensitive and exposed to a number of hazards and associated loss to crops. Recent climate projections by the Intergovernmental Panel on Climate Change (IPCC) and other global agencies indicate an increase in extreme weather events, posing a potential risk to farming globally and particularly in developing countries like India. These risks include climate and weather-related threats, natural disasters, and the spread of pests and diseases, all of which contribute to highly variable crop yields. According to the Indian Agricultural Research Institute (IARI), rabi crops in India are expected to suffer greater losses than kharif crops as a possible impact of projected climate change. Temperature of above 18 ºC to 22 ºC during jointing and anthesis stages in December and January can trigger leaf blight in wheat in Haryana. Additionally, heavy rainfall followed by prolonged periods of bright sunshine in March and April can lead to the pre-ripening of wheat, resulting in a reduction in grain weight. High temperature and high humidity can cause a number of diseases outbreak in rice crop in the region. Fungal induced diseases including sheath blast, smut and grain discoloration have been found more in rice crop than wheat crop in Haryana. In light of changing climatic conditions, it is crucial to develop a range of physical, chemical, and biological methods for controlling crop diseases and associated risks. Integrated crop disease management practices should include the use of both chemical and bio/organic products to protect crops from diseases. It includes regular monitoring of symptoms of disease outbreak, assessment of soil nutrient composition, adoption and in-situ management of green manure in the soil, a judicious, balanced and need based use of fertilizers/ pesticides. This study focuses on developing an integrated risk assessment and management module at the community level in Haryana. It involves assessing the risks posed by extreme by extreme climatic conditions and implementing risk management measures at the community level.